Investigation of the existing methodology of value estimation and methods of discount rate estimation - Plikus, Iryna (Technology audit and production reserves, 2017)
The subject of research is the current practice of determining the fair value of assets and liabilities at the present (discounted) cost. One of the most problematic places is the determination of the discount rate, which belongs to the jurisdiction of a professional accountant judgment. The methods of formalization, hypothetical assumption, system approach and scientific abstraction in substantiating the formation of accounting policy with respect to the choice of the discount rate are used in the research. The results of the study have shown that fair value measurement using discounting can reduce the quality of financial reporting for subjectivity when choosing methods for its valuation and the discount rate. An algorithm is proposed in the choice of methods for fair value estimation, which allows to more reliably determine the real value of accounting objects and elements of financial reporting. Thanks to this, it is possible to simulate the process of calculating the cost of objects, by sequentially identifying an adjustment to the aggregation of value values. Proceeding from the desire to minimize the influence of professional judgments on the financial reporting indicators, the feasibility of determining the future cash flow with the terms of the contract is justified. For the purposes of the following estimates of this asset or liability, it is necessary to calculate the discount rate. Based on the mathematical dependence of the present value of the future cash flow with its nominal value and the discount rate, a formula for calculating the discount rate is proposed. In comparison with similar studies, such discount rate is the actual rate agreed by the parties to the contract, agreeing on the terms and amount of payments. This provides an opportunity to minimize the impact of professional accounting judgments on the reliability level of financial reporting.